ANALISIS ANALISIS KEAKTIFAN BELAJAR SISWA TERHADAP MODEL PEMBELAJARAN HYBRID LEARNING KELAS VII DI SMPN 2 PASIR PENYU - Puji Astuti; Yaya Naufa Khairiyah; Wulida Arina Najwa (Program Studi Pendidikan Guru Sekolah Dasar STKIP Al Hikmah Surabaya, 2023)
The background of the problem in this study is the lack of active student learning in the learning process. To see the activeness of student learning the teacher uses a learning model, namely the Hybrid Learning model. The Hybrid Learning model can be used to increase student learning activity and can eliminate student boredom in receiving material delivered by educators, especially in the current situation. Hybrid Learning models can be used in online learning processes so that students can carry out the learning process even if only at home or at school with limited time. This research is a descriptive qualitative research (descriptive research) in which the research method is to collect data in the form of words, pictures, not numbers and all that is collected is likely to be the key to what is being studied. The subjects of this study were selected based on students' daily scores on the previous material, namely lines and angles, in which the subjects of this study included 5 students, 3 of whom had the highest daily scores and 2 of them had the lowest daily scores. Data collection techniques are observation, Focus Group Discussion (FGD), documentation. Furthermore, the data obtained will be analyzed based on indicators of student learning activity. The data analysis technique in this study is by reducing data, presenting data, and verifying data. Based on the final results of the questionnaire score, namely 31% chose to strongly agree, 26% chose to agree, 27% chose to be undecided, 11% chose to disagree, and 5% chose to strongly disagree and the results of interviews using the Hybrid Learning model students became more active during the learning process. So it can be concluded that student learning activity is good.